Burnout as a psychological disorder in competitive athletics - Krippl, Martin; Ziemainz, Heiko (Advances in Psychology Research 69, 2010)
The growing interest in the burnout syndrome in the field of athletic science is a recent phenomenon (Kallus & Kellmann, 2000). The study to be reviewed here involved the long-term use of a questionnaire and altogether 363 competitive athletes, and purports to apply predictive parameters from the transactional model (Lazarus, 1992) and the conservation of resources theory (see, for example, Hobfoll, 2001) in order to predict three dimensions of burnout. We applied the German version of the Athlete Burnout Questionnaire (ABQ, Raedeke & Smith, 2001), which distinguishes three dimensions: “emotional/physical exhaustion” (Burnout-E), “reduced sense of accomplishment” (Burnout-RA) and “sports devaluation” (Burnout-D). Because the three dimensions show clearly different courses of development, they will be analyzed here for the first time individually. For each of the burnout subscales a linear regression was computed with the following group variables: personality factors, motivation (MOMS), environmental factors, resource losses (COR-E-G), resource gains (COR-E-G), stress regulation styles (SVF), and discomfort. Results demonstrate for all the burnout subscales that trait anxiety has the strongest effect and enjoyment has a strong one. An influence from “resource gains” could be seen only for “sports devaluation”. Analysis showed that losses in self-confidence were the only relevant resource loss for the subscale emotional-physical exhaustion.
UnivIS-Import:2017-12-18:Pub.2010.phil.dss.lsw.burnou
Keywords: Burnout; Competitive athletes; Conservation of resources theory